Active radio : Pacifica's brash experiment - Land, Jeff (Commerce and mass culture series., 1999)
In April 1949, KPFA in Berkeley, California, went on the air. From the beginning, the station broadcast an utterly new combination of political commentary and cultural discussion, dedicated to creative expression and dissent. In this fascinating account, Jeff Land tells the heroic story of the Pacifica radio network and the practical model it pioneered for liberatory alternatives to commercial mass media.